Report on Torres Strait Fisheries Research Protocols A Guide for Researchers ﻿ - Nakata, Martin (UTS ePRESS, 2011)
At its 45th meeting in 2008, the Torres Strait Scientific Advisory Committee (TSSAC) set down for discussion the need for guiding protocols that researchers adopt when working in the Torres Strait (45.6.1). The Committee considered the current processes and procedures for fisheries research in the Torres Strait, and discussed approaches developed for other organisations. At the following meeting members agreed to commission a review of current approaches and the development of a single source web-based document that would provide guiding protocols for adoption by researchers when working in the Torres Strait. This book is the result of the commissioned work.